Penerapan p-Median terhadap optimasi alokasi dan lokasi distribution center pada Sistem Logistik Pedesaan di Indonesia - Ely Asmara; Bonivasius Prasetya Ichtiarto (Universitas Mercu Buana, 2021)
Every village has Village Superior Products (Prudes) which have economic value that can advance the economy of rural communities. However, the consolidation of the Prudes results is still not optimal, it can be seen from the poverty rate in rural areas which is still high when compared to the level of poverty in the city. To overcome this, it requires the efficiency and effectiveness of distribution centers in rural supply chain systems in order to consolidate the Prudes products from a number of villages to a number of customers/consumers. However, the main problem is how many distribution centers are needed and where are the distribution centers located in an area that has the same type of Prudes. Therefore, the aim of this research is to find the best location P from a number of candidates distribution centers (N = 59 villages) where P ≤ N. To achieve the objectives of this study, the P-Median method is used with the help of AMPL software as a data processing tool. in order to complete the model of the P-Median. The objective function of the P-Median model is to find the minimum value of the total cost based on distance (), production volume (), shipping costs (), and fixed cost () at a number of DC facilities. In the process before the completion of the P-Median model, the approach is first carried out proximity analysis which consists of the pre-qualification and qualification processes in determining candidate facility candidates distribution center. This approach was taken to cover the limitations of APML software in processing data. The result of this research is that the optimal number of DC facilities in five DC facilities with a total cost minimum of IDR 91.80 billion. Meanwhile, the facilities are distribution center located in the village of Sanuanggamo, North Tongauna District (P11), Awuliti Village, Lambuya District (P17), Mumundowu Village, Pondidaha District (P36), Duriasi Village, Wonggeduku District (P44), and Puday Village, West Wonggeduku District (P53).